Liquid formulation of halo-alkali-thermo-tolerant rhizobacteria for enhanced growth of mung bean crops under abiotic stresses - Nishtha R. Vaghela; Sangeeta D. Gohel (Scientific Reports)
Abstract The saline rhizosphere of arid regions harbors diverse microbial communities that play a crucial role in plant growth and abiotic stress mitigation. Salinity is a major constraint for crop productivity, particularly affecting salt-sensitive crops like mung bean (Vigna radiata L.). In this study, plant growth-promoting rhizobacteria (PGPR) such as Streptomyces sp. KhEc 44, Bacillus paralicheniformis KhEc 68, and Priestia filamentosa KhEc 69 were isolated from the rhizospheric soil of Euphorbia caducifolia L. growing in the saline-alkaline soils of Kharaghoda, Little Rann of Kutch, Gujarat (India). These strains were evaluated for key PGPR traits including indole-3-acetic acid (IAA) synthesis, siderophore production, and phosphate solubilization. These isolates exhibited growth at 2 M NaCl (w/v), pH 10, and 60 °C, confirming their halo-, alkali-, and thermo-tolerant nature. Additionally, the strains demonstrated extracellular amylase production up to 17% NaCl (w/v). Greenhouse experiments showed that inoculation with these stress-tolerant PGPR significantly enhanced mung bean growth parameters even under 120 mM NaCl stress. Plants treated with the formulated liquid biofertilizer exhibited improved growth, biomass, and tolerance compared to untreated controls. This study demonstrates the potential of using a liquid biofertilizer composed of multi-stress-tolerant PGPR to improve mung bean productivity under both normal and saline-alkaline field conditions.